Size Effect of Chevrel MgxMo6S8 as Cathode Material for Magnesium Rechargeable Batteries - Cho, Woosuk; Moon, Bora; Woo, Sang-Gil; Kim, Jae-Hun; Park, Min-Sik; Kim, Jeom-Soo; Kim, Hansu; Kim, Young-Jun (Bulletin of the Korean Chemical Society, 2015)
Submicrosized chevrel Mo6S8 powder is synthesized using mechanical milling of the starting materials and the powder yield is increased by using modified synthesis method. The effect of particle size is investigated using various electrochemical techniques. The submicrosized chevrel shows enhanced discharge capacity compared with that of microsized chevrel, and voltage profile indicates that the low capacity arising from Mg trapping at the Mg‐1 site is improved for submicrosized chevrel. Mg trapping is also verified by ex situ X‐ray diffraction measurement and the results are in good agreement with the electrochemical profile. Open‐circuit voltage measurements and AC‐impedance spectroscopy are used to identify the kinetics of Mg2+ insertion. The improved electrochemical properties obtained with the submicrosized chevrel are attributed to the smaller particles that provide shorter diffusion lengths for Mg2+ ions.